Surface integrity of grinding-assisted chemical etching (GACE). Issue 1 (October 2016) - Bahrami, Pooya; Azizi, Abdolhamid
Abstract Grinding-assisted chemical etching (GACE) is hybrid machining process, which combines the chemical and mechanical (grinding) machining. The features of this process are the ability to grinding nonferrous metals and improved surface finishing in comparison with typical grinding. In this study, attempts to grinding Al-EN AW-7075 with FeCl3 etchant and the integrity of the machined surface have been discussed. It was observed that by applying the GACE operation in grinding of aluminum, surface roughness decreased. Comparative observations are made, in order to show the potential of the present process modifications to improve the productivity during grinding Al-EN AW-7075 in relation to the conventional methods.